Supply-side constraints, capital goods imports, and the quality of Sub-Saharan African countries' exports - Catherine Y. Co (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
In the last decade, a large portion of capital goods imports of Sub-Saharan African countries is telecommunications equipment, and China is now the main source of equipment for 30 Sub-Saharan African countries. A connection between specific types of equipment imports and subsequent exports is found with elasticity estimates ranging from 0.2 to 1.2 per cent. Estimates show that controlling for price, the estimated quality of Sub-Saharan African countries' exports is lower than that of their peers. This means that if Sub-Saharan African export prices were to increase, their US market share would suffer despite the price advantage provided by the African Growth Opportunity Act.
Keywords: F14; O24; 330; capital goods; product quality; Sub-Saharan Africa; African Growth Opportunity Act